2008
DOI: 10.1056/nejmoa063564
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus for Angiomyolipoma in Tuberous Sclerosis Complex or Lymphangioleiomyomatosis

Abstract: Background-Angiomyolipomas in patients with the tuberous sclerosis complex or sporadic lymphangioleiomyomatosis are associated with mutations in tuberous sclerosis genes resulting in constitutive activation of the mammalian target of rapamycin (mTOR). The drug sirolimus suppresses mTOR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
977
1
41

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,147 publications
(1,043 citation statements)
references
References 32 publications
24
977
1
41
Order By: Relevance
“…As mentioned previously, limited data suggest that mTOR inhibitors may require continuous use to maintain reductions in TSC‐associated tumors 11, 12. In our study, regrowth of SEGA was observed in 1 patient who had previously met the criteria for treatment success (75% reduction in SEGA volume) at 18 months and then discontinued everolimus.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…As mentioned previously, limited data suggest that mTOR inhibitors may require continuous use to maintain reductions in TSC‐associated tumors 11, 12. In our study, regrowth of SEGA was observed in 1 patient who had previously met the criteria for treatment success (75% reduction in SEGA volume) at 18 months and then discontinued everolimus.…”
Section: Discussionsupporting
confidence: 62%
“…Patients with TSC typically have comorbidities that reflect the involvement of multiple organs. Unlike a neurosurgical procedure, mTOR inhibitor therapy may cause regression of other lesions, such as angiomyolipomas (kidney), angiofibromas (skin), and lymphangioleiomyomatosis (lung) 12, 22, 23, 24, 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the first formal prospective phase I/II open-label clinical trial of sirolimus therapy for patients with TSC or sporadic LAM, in which both are associated with AML development, were published in 2008 (Bissler et al, 2008). A cohort of 25 adult patients, 19 with TSC (of who 12 had LAM) and 6 with sporadic LAM, were treated with sirolimus (5-15 ng/ml) for 1 year, followed by a 12-month follow-up period.…”
Section: The Mtorc1 Inhibitors As Treatment For Tscmentioning
confidence: 99%
“…Total regression of lesions due to rapamycin therapy has never been observed, except for facial angiofibromas and erythema treated with topical administration of sirolimus (Kaufman McNamara et al, 2010). In fact, tumor regrowth occurred following cessation of therapy (Franz et al, 2006;Wienecke et al, 2006;Bissler et al, 2008). These observations would implicate a life-long treatment with rapamycin, but little is known yet about long-term effects or complications of the drug.…”
Section: The Mtorc1 Inhibitors As Treatment For Tscmentioning
confidence: 99%